2021
DOI: 10.3390/ijerph18136718
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Back Condition and the Level of Physical Activity as Well as Internet Addiction among Physiotherapy Students during the COVID-19 Pandemic in Poland

Abstract: Objectives: The aim of this study was to assess back pain and its relation to physical activity as well as Internet addiction among Polish university students during the COVID-19 pandemic. Methods: The research was conducted via the Internet in student groups of three universities in Poland (141 people). Back pain was examined by ODI—The Oswestry Disability Index and NDI—Neck Disability Index. The Polish-language International Physical Activity Questionnaire (IPAQ) was used to assess physical activity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Pain, which has physical, psychological, and social aspects, is a potential risk for the development of musculoskeletal problems for students (Salameh et al, 2022). During the Covid‐19 lockdown period, prior studies have noted that technological device use, social isolation, and distance education caused discomfort in the shoulder and back region of students (Gałczyk et al, 2021; Roggio et al, 2021; Salameh et al, 2022). The results of previous studies indicated that students' prevalence of pain was raised in the cervical and lumbar regions during the Covid‐19 lockdown (Gałczyk et al, 2021; Leirós‐Rodríguez et al, 2020; Salameh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain, which has physical, psychological, and social aspects, is a potential risk for the development of musculoskeletal problems for students (Salameh et al, 2022). During the Covid‐19 lockdown period, prior studies have noted that technological device use, social isolation, and distance education caused discomfort in the shoulder and back region of students (Gałczyk et al, 2021; Roggio et al, 2021; Salameh et al, 2022). The results of previous studies indicated that students' prevalence of pain was raised in the cervical and lumbar regions during the Covid‐19 lockdown (Gałczyk et al, 2021; Leirós‐Rodríguez et al, 2020; Salameh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…During the Covid‐19 lockdown period, prior studies have noted that technological device use, social isolation, and distance education caused discomfort in the shoulder and back region of students (Gałczyk et al, 2021; Roggio et al, 2021; Salameh et al, 2022). The results of previous studies indicated that students' prevalence of pain was raised in the cervical and lumbar regions during the Covid‐19 lockdown (Gałczyk et al, 2021; Leirós‐Rodríguez et al, 2020; Salameh et al, 2022). Previous reports demonstrated that the frequency of neck pain was between 43.5% to 65% in students (Roggio et al, 2021; Salameh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The recent COVID experience has exacerbated this risk of 'psychological stress' for workers who may feel 'stuck at work' even though they are at home [67]. Another stream of research regarding disadvantages of working from home concerns the lower level of physical activities and physical pain, e.g., in the back [68,69].…”
Section: Potential Benefits Enabling Factors and Barriers To Wfhmentioning
confidence: 99%
“… 21 Several factors have been further associated with internet addiction during the COVID-19 pandemic, such as depression, anxiety, musculoskeletal pain and a decrease in physical activity, and even lower levels of self-reported health especially among students. 18 , 22 …”
Section: Introductionmentioning
confidence: 99%